2014
DOI: 10.14444/1021
|View full text |Cite
|
Sign up to set email alerts
|

Transforaminal Endoscopic Lumbar Decompression & Foraminoplasty: A 10 Year prospective survivability outcome study of the treatment of foraminal stenosis and failed back surgery

Abstract: BackgroundConventional diagnosis between axial and foraminal stenosis is suboptimal and long-term outcomes limited to posterior decompression. Aware state Transforaminal Endoscopic Lumbar Decompression and Foraminoplasty (TELDF) offers a direct aware state means of localizing and treating neuro-claudicant back pain, referred pain and weakness associated with stenosis failing to respond to conventional rehabilitation, pain management or surgery. This prospective survivability study examines the outcomes 10 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 35 publications
(25 reference statements)
2
48
2
Order By: Relevance
“…Two weeks after the treatment with oral neurotrophic drugs and nonsteroidal anti‐inflammatory therapy, the symptoms were completely relieved. Knight et al . reported that transient post‐operative “flares” were noted in 19% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two weeks after the treatment with oral neurotrophic drugs and nonsteroidal anti‐inflammatory therapy, the symptoms were completely relieved. Knight et al . reported that transient post‐operative “flares” were noted in 19% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…first described the transforaminal arthroscopic decompression of lateral recess stenosis in 1996. In 2014, Knight et al . and Lewandrowski described PTED is a beneficial intervention for the treatment of spinal or foraminal stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic foraminoplasty with a side-firing laser, high-speed burr, trephine, or reamer, etc. has been proven to be a safe procedure to widen the lumbar foramen by removing part of bone and ligamentous tissue surrounding the foramen (17,(24)(25)(26)(27)(28). However, the disadvantages of endoscopic foraminoplasty are quite obvious, for example, expensive equipment, low working efficiency, inadequate decompression for lateral recess stenosis, and risk of heat-damage to surrounding spinal nerves (11,12,15,16).…”
Section: Safety Of a Specially Designed Instrument For Modified Plfmentioning
confidence: 99%
“…Besides, the increase in temperature while using a highspeed burr or side-firing laser may potentially lead to inflammation of the nerve and may also cause deterioration of nerve conduction to some extent (15,16). Knight et al (17) reported that transient post-operative "flares" were noted in 19% of patients when a sidefire laser was used in transforaminal endoscopic lumbar foraminoplasty for foraminal stenosis, while Ahn et al (18) reported 6.1% postoperative dysesthesia after endoscopic foraminotomy with an endoscopic high-speed drill. The disadvantages of endoscopic foraminoplasty also include a steep learning curve and need of expensive equipment.…”
mentioning
confidence: 99%
“…There were no permanent complications, but temporary dysesthesia indicated irritation of the DRG. Knight et al 29 reported that transient postoperative "flares" were noted in 15 (19%) of 79; they were a transient recurrence of the patient's predominant presenting symptoms beginning a week after surgery and lasting 2 to 4 weeks. Theoretically, nerve compression injury is likely to occur if the 8-mm cannula is inserted in the very narrow intervertebral foramen.…”
Section: Complicationsmentioning
confidence: 99%